A Legal History of Legal History in England and Wales - Ireland, Richard W. (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
This article explores the development of the study of legal history as a subject in the law schools of England and Wales. It outlines changes in university education more generally, and in legal scholarship in particular and how those changes impact the particular subject under study. Drawing on empirical studies and personal reflections relating to past experience it concludes by speculating on potential different outcomes, both positive and negative, which may emerge when the universities of England and Wales emerge from the uncertainty of the COVID-19 pandemic, during which the piece was written.